FTY720 Inhibits the Development of Collagen-Induced Arthritis in Mice by Suppressing the Recruitment of CD4+ T Lymphocytes - Zhu C; Wen S; Li J; Meng H; Zhang J; Zhao K; Wang L; Zhang Y (Dove Medical Press, 2021)
Chao Zhu,1– 5 Shuang Wen,6 Junyong Li,1– 3,5 Hongyu Meng,1– 3,5 Junzhe Zhang,1– 3,5 Kuo Zhao,1– 3,5 Ling Wang,1– 3,5 Yingze Zhang1– 3,5,7 1Department of Orthopaedic Surgery, Third Hospital of Hebei Medical University, Shijiazhuang, People’s Republic of China; 2Key Laboratory of Biomechanics of Hebei Province, Shijiazhuang, People’s Republic of China; 3NHC Key Laboratory of Intelligent Orthopaedic Equipment, Third Hospital of Hebei Medical University, Shijiazhuang, People’s Republic of China; 4Department of Orthopedics, The Affiliated Jiangning Hospital with Nanjing Medical University, Nanjing, People’s Republic of China; 5Orthopaedic Research Institution of Hebei Province, Shijiazhuang, People’s Republic of China; 6Department of Immunology, Nanjing Medical University, Nanjing, People’s Republic of China; 7Chinese Academy of Engineering, Beijing, People’s Republic of ChinaCorrespondence: Yingze Zhang Email suryzz@163.comBackground: Fingolimod (FTY720), a novel immunomodulator, was found to suppress the severity of collagen-induced arthritis (CIA) in mice. However, the potential molecular mechanisms are still unknown, and the effect of FTY720 on the recruitment of immune cells in the affected joints in the CIA model is not clear.Materials and Methods: Following the oral administration of FTY720 (2 mg/kg) was treated into CIA mice per day for 35 days, intravital microscopy and immunofluorescence assays were performed to examine immune cell recruitment in the affected joints. Human MH7A synoviocytes were stimulated with tumour necrosis factor (TNF)-α and incubated with FTY720. Interleukin-1β (IL-1β), interleukin-6 (IL-6), and interleukin-8 (IL-8) mRNA and protein expression were evaluated using RT-PCR and enzyme-linked immunosorbent assay, respectively. Signal transduction pathway protein expression was measured by Western blotting. Nuclear translocation of nuclear factor (NF)-κB was also analyzed by fluorescence microscopy.Results: In vivo experiments showed that FTY720 inhibited the recruitment of CD4+ lymphocytes in the affected joints of CIA mice. FTY720 reduced the secretion of IL-1β, IL-6, and IL-8 from TNF-α-stimulated MH7A cells in a dose-dependent manner. FTY720 also inhibited TNF-α-induced phosphorylation of NF-κBp65 and IκBα, as well as NF-κBp65 nuclear translocation, in a dose- and time-dependent manner. Interestingly, FTY720 blocked PI3K/Akt, the upstream targets of the NF-κB pathway.Conclusion: Our findings demonstrated that oral administration of FTY720 exerted beneficial effects in CIA mice by inhibiting CD4+ T lymphocyte recruitment to the affected joints. Our data also indicated that FTY720 inhibited TNF-α-induced inflammation by suppressing the AKT/PI3K/NF-κB pathway in MH7A cells.Keywords: FTY720, rheumatoid arthritis, NF-κB, MH7A, CD4+ T lymphocytes